2003
DOI: 10.1002/joc.942
|View full text |Cite
|
Sign up to set email alerts
|

The annual cycle and interannual variability of atmospheric pressure in the vicinity of the North Pole

Abstract: A comparison of National Centers for Environmental Prediction-National Center for Atmospheric Research reanalysis six-hourly sea-level pressure data with former Soviet drifting station observations over the central Arctic Basin reveals high monthly correlations throughout the period 1950-91, but also a preferred winter season negative bias of about 1.4 hPa. Using the reanalysis, supplemented by Arctic Ocean Buoy Program fields and in situ observations, a generalized depiction of the annual cycle of pressure fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 52 publications
5
11
0
Order By: Relevance
“…In the record of high-wind events in the Chukchi-Beaufort region from 1945 to the present, the frequency of storms was relatively low from the late 1960s through the mid 1980s, though higher before and after that period (Lynch at al., 2004). This pattern is consistent with the dramatic shift toward low-pressure systems over the central Arctic Basin observed in the late 1980s, resulting from the shift of a largescale air mass to the North Pacific (Walsh et al, 1996;Cullather and Lynch, 2003).…”
Section: The Larger Contextsupporting
confidence: 74%
“…In the record of high-wind events in the Chukchi-Beaufort region from 1945 to the present, the frequency of storms was relatively low from the late 1960s through the mid 1980s, though higher before and after that period (Lynch at al., 2004). This pattern is consistent with the dramatic shift toward low-pressure systems over the central Arctic Basin observed in the late 1980s, resulting from the shift of a largescale air mass to the North Pacific (Walsh et al, 1996;Cullather and Lynch, 2003).…”
Section: The Larger Contextsupporting
confidence: 74%
“…The geostrophic wind speed derived from NCEP re-analysis SLP at high latitude is usually underestimated by about 8%. [This bias, however, is not significant (Cullather and Lynch 2003;Smith et al 2001;Wylie 2001).] This may translate into an underestimation of the wind stress by about 15%.…”
Section: ͑8͒mentioning
confidence: 97%
“…This latitude-longitude dataset was reprojected to the National Meteorological Center 47 × 51 octagonal grid, so that each data point is approximately equidistant to the surrounding points, with a nominal grid spacing of 190.5 km. Cullather & Lynch (2003) compared NCEP/NCAR Reanalysis SLP data with drifting camp measurements in the Arctic Ocean and found high correlations, although significant seasonal discrepancies with a cold season bias were evident. Further, while they were able to qualitatively reproduce their results using the Arctic Ocean Buoy Program (AOBP) data set, an optimal interpolation of Arctic buoy data and the drifting camp data, they concluded that shortcomings remain which require that error bounds of up to 2 hPa be taken into account.…”
Section: Datamentioning
confidence: 99%